Preproopiomelanocortin and preprodynorphin mRNA expressions in rat brain after electroacupuncture + droperidol - Zhu Chong-Bin; Li Xiao-Yu; Zhu Yan-Hua; Xu Shao-Fen (Acta Pharmacologica Sinica, 2016)
AIM: To study the expression of preproopiomelanocortin (POMC) and preprodynorphin (PPD) mRNA following the combination of electroacupuncture (EA) with droperidol (Dro), a dopamine receptor antagonist. METHODS: The brains and spinal cords of Sprague-Dawley rats were sectioned after combination of EA with Dro, and the gene expression was investigated using nonradioactive in situ hybridization histochemistry (ISHH). RESULTS: Ten hours after EA, the POMC mRNA expression was enhanced; the expression was further enhanced when EA was combined with Dro. The expression of PPD mRNA showed regional difference in central nervous system (CNS): in spinal cord, EA enhanced the PPD mRNA expression and the combination of EA with Dro further promoted the expression; in the brain, the PPD mRNA expression after EA or combination of EA with Dro showed no obvious change in most regions (caudate-putamen, accumbens, arcuate nucleus of hypothalamus) or was decreased in supraoptic nucleus. CONCLUSION: Dro combined with EA promoted the expression of POMC mRNA in CNS and PPD mRNA in spinal cord, but reduced or had no effect on PPD mRNA expression in the brain.